Geração e difusão do conhecimento : estudo dos relacionamentos no processo de internacionalização da Chery Brasil - Françoso, Ana Beatriz Lopes (Universidade Federal de São Carlos, 2017)
When it comes to internalization of companies, there are several factors that drive companies to venture into new markets, such as the increasement of the competition and the facilities of trade and production in other countries. However it is indispensable that the company knows the market in which it will operate. And one of the ways is to establish new relationships with agents in the new country, and so acquire new knowledge that will contribute to the evolution of the internationalization’s process of the company in the new country. This research refers, then to the understanding of how occurs the generation and dissemination of knowledge that is acquired from the relationship inter and intra-organizational level which changes the operation’s mode of the multinational company by the time, within its internationalization process. Through the behavioral theories such as the model of Uppsala, the literature of subsidiaries’ development and relational model, it was possible to analyze the relationships that were articulate by the company and analyze the knowledge for it acquired and disseminated. To conduct the research, a unique case study of qualitative nature was developed, under a longitudinal perspective, which involved a Brazilian subsidiary called Chery Brazil Manufacture Importation and Distribution Ltda., which the head office is a Chinese origin. This present research showed that it is evident that in its internationalization path, the relationships inter and intra-organizational were fundamental to Cherry Brazil, regarding the generation and dissemination of different type of knowledge and these were decisive for the modification of its mode of operation, which secured their stay in the country.
Keywords: Relacionamento; Conhecimento; Modo de operação; Internacionalização; Chery Brasil; Relationship; Knowledge; Mode of operation; Internationalization; ENGENHARIAS::ENGENHARIA DE PRODUCAO